2022
DOI: 10.1021/acs.orglett.2c00495
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal Promiscuous UbiA Prenyltransferase Expands the Structural Diversity of Chrodrimanin-Type Meroterpenoids

Abstract: Prenyltransferases play important roles in the diversification of natural products and the improvement of biological activities. A UbiA-type prenyltransferase CdnC with substrate promiscuity was identified as the pivotal builder of the noncanonical chrodrimanin skeletons, which carry a benzocyclohexanone structure as the nonterpene part. In vitro and heterologous expression studies with CdnC led to the production of a series of novel chrodrimanin-like structures. The discovery of CdnC offers a referable strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Comprehensive analyses depending on the sequence similarity network (SSN), [9] sequence characterization and phylogenetic tree showed that 1) CosA and its homologous proteins belong to a separate UbiA‐type PT clade (Figure 3a); [10] 2) both motif 2 YxxxK and motif 3 DxxxD are conserved in the classical UbiA‐type PTs and CosA family enzymes; however, the classical motif 1 N/DDxxDxxxD was mutated to VDxxDxxxD in CosA and its homologous proteins (Figure 3b); [11] and 3) the substrate recognition of CosA is far from the well‐known UbiA‐type PTs of meroterpene compounds (Figure 3b). [3d,12] …”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive analyses depending on the sequence similarity network (SSN), [9] sequence characterization and phylogenetic tree showed that 1) CosA and its homologous proteins belong to a separate UbiA‐type PT clade (Figure 3a); [10] 2) both motif 2 YxxxK and motif 3 DxxxD are conserved in the classical UbiA‐type PTs and CosA family enzymes; however, the classical motif 1 N/DDxxDxxxD was mutated to VDxxDxxxD in CosA and its homologous proteins (Figure 3b); [11] and 3) the substrate recognition of CosA is far from the well‐known UbiA‐type PTs of meroterpene compounds (Figure 3b). [3d,12] …”
Section: Resultsmentioning
confidence: 99%
“…Figure S1 displays the NPs formed from the crosstalk of separate BGCs. Echinocandin B and chrodrimanin I are synthesized via assembly line insertion of core structural elements from other BGCs, with identified specific enzymes. , The remaining structures illustrate the direct coupling between blocks derived from the separate BGCs. Amodesmycin A and azasperpyranone A are generated through specific enzymes, and penilactone B results from nonenzymatic spontaneous coupling, whereas enzymatic involvement in others remains uncertain .…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the conventional synthesis by a single biosynthetic gene cluster (BGC), hybrid NPs (hbNPs) are constructed via a heterocoupling of structurally diverse precursors from separate BGCs, enhancing chemical diversity and expanding their potential as drug leads (Figure S1A). Such functional crosstalk between BGCs involves both enzymatic and spontaneous nonenzymatic reactions, such as those leading to azasperpyranone A and penilactone B, which has proven crucial for generating compounds with unique biological activities (Figures A and S1B for other examples). Here, we activated the silent BGCs in a halophyte Suaeda salsa-derived Penicillium citrinum HDN11–186, which led to the discovery of three novel hbNPs with unique skeletons formed through crosstalk of highly reactive blocks from separate BGCs: sorbremnoid A ( 1 ), which directly binds to the NLRP3 protein, sorbremnoid B ( 2 ) and sorbtalone ( 3 ) (Figures B and A). The pseudonatural products’ (PNPs’) strategy, a human-driven evolution of NPs, has provided chemically diverse classes enabling the exploration of biologically relevant chemical space through the fusion of NP fragments in various combinations and arrangements. , Biology-oriented synthesis and chemoinformatic tools have guided the establishment of PNP libraries that cannot be accessed in nature. , In this study, the discovery of compounds 1 , 2 , and 3 proved that artificial intervention, modifying blocks in microbial metabolism and various enzymes, can effectively promote the generation of novel fusion skeletons via BGC crosstalk that does not occur naturally.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme crystal structure analysis and AI structure prediction also facilitated these investigations. Besides terpene cyclases and αKG-dependent dioxygenases, P450 monooxygenases and UbiA-type prenyltransferases have also expanded the variety of meroterpenoids [ 41 42 ]. These untapped membrane enzymes will be applicable for engineered biosynthesis, with structural models providing useful information for mutagenesis, as in the engineering of meroterpenoid cyclases [ 11 ] and fungal P450 oxygenases catalyzing cross-coupling between two aromatic rings [ 43 ].…”
Section: Discussionmentioning
confidence: 99%